2019
DOI: 10.21203/rs.2.12212/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Preventive Behaviors of Hepatitis B among Nurses; Insights from the Theory of Planned Behavior

Abstract: Background Hepatitis B is the cause of the majority of acute and chronic infections, liver cirrhosis and liver cancer in the world. The purpose of current research was to investigation the hepatitis B (HB) preventive behaviors in nurses in west of Iran by using the theory of planned behavior (TPB). Methods This cross-sectional research was conducted on 330 nurses from five teaching and treatment hospitals in Kermanshah who were randomly selected. Data were collected by self-report questionnaire. Data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As the most effective and standardized screening method, mammography is necessary for achieving the highest level of success in breast cancer screening (Mirzaei-Alavijeh et al, 2018). Findings from previous studies indicated that older women undertake mammography screening much more than younger ones (Yusof et al, 2014;Mirzaei-Alavijeh et al, 2018). This discrepancy should never exist as a baseline mammogram should be obtained by age 40, with yearly mammogram after the age of 40 (George, 2000).…”
Section: Validity and Reliability Of Health Belief Model Questionnairmentioning
confidence: 99%
“…As the most effective and standardized screening method, mammography is necessary for achieving the highest level of success in breast cancer screening (Mirzaei-Alavijeh et al, 2018). Findings from previous studies indicated that older women undertake mammography screening much more than younger ones (Yusof et al, 2014;Mirzaei-Alavijeh et al, 2018). This discrepancy should never exist as a baseline mammogram should be obtained by age 40, with yearly mammogram after the age of 40 (George, 2000).…”
Section: Validity and Reliability Of Health Belief Model Questionnairmentioning
confidence: 99%